The Relationship between Climate-Responsive Public Expenditure, Economic Growth and Environmental Performance: Evidence from Nepal (2013–2022) - Bhattarai, Aayush; Dhakal, Kamal (Janaprakash Journal of Multidisciplinary Research, 2025)
This paper investigates the relationship between CRPE, economic growth, and environmental performance proxy by per capita CO2 emissions in Nepal from 2013 to 2022. Data sourced from the World Bank, EDGAR, and the Climate Budget Tagging at the Ministry of Finance are analyzed using Augmented Dickey–Fuller, Engle–Granger, OLS, and Unrestricted Distributed Lag models. Both CRPE and GDP have a positive effect on emissions, with elasticities being 0.63 and 1.40, respectively, indicating that Nepal remains in the rising phase of the EKC. At the same time, CRPE supports growth with elasticity 0.404, while environmental impacts may appear with a lag, which corresponds with the delayed effects of public investment according to the UDL model. The lack of a long-run equilibrium means that the dynamics of the model are dominated by the short run. Findings suggests Policy makers in developing countries to particularly focus on low-carbon investments and incorporate emission-reduction goals in fiscal policy frameworks to attain green, sustainable, and inclusive growth.